2007
DOI: 10.3174/ajnr.a0586
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Metabolic Indices in Regions of Abnormal Perfusion in Patients with High-Grade Glioma

Abstract: BACKGROUND AND PURPOSE: MR spectroscopic imaging (MRSI) and dynamic susceptibility-contrast MR imaging (DSC-MR imaging) are functional in vivo techniques for assessing tumor metabolism and vasculature characteristics. Because tumor hypoxia is influenced by tortuous, degraded, swollen, and angiogenic tumor vasculature, regions of abnormal perfusion parameters should coexist with changes in lactate and creatine metabolite levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 31 publications
(38 reference statements)
0
22
0
Order By: Relevance
“…Peritumoral edema showed significantly lower values of this metabolite ratio than the solid tumor part, but with respect to the tumor center, the significance was not confirmed. The lowest values of the Lac/tCr among all investigated brain areas were observed in the healthy tissue, taking into account that the only nonsignificant differences were related to the peritumoral a high tumor cells proliferation and thus also increased density of cell membranes in tumorous tissue area (Lupo et al 2007;Schneider et al 2010;Marie and Shinjo 2011). Membrane phospholipids are beneficial for spectroscopic tumor detection.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Peritumoral edema showed significantly lower values of this metabolite ratio than the solid tumor part, but with respect to the tumor center, the significance was not confirmed. The lowest values of the Lac/tCr among all investigated brain areas were observed in the healthy tissue, taking into account that the only nonsignificant differences were related to the peritumoral a high tumor cells proliferation and thus also increased density of cell membranes in tumorous tissue area (Lupo et al 2007;Schneider et al 2010;Marie and Shinjo 2011). Membrane phospholipids are beneficial for spectroscopic tumor detection.…”
Section: Resultsmentioning
confidence: 92%
“…However, it is possible to spectroscopically measure precursors of their synthesis and products of their degradation as the tCho signal contributors (Solivera and Law 2009;Ha et al 2013). Since the level of tCho particularly reflects the concentration of phosphocholine which is more than twice increased in highgrade gliomas (Lupo et al 2007;McKnight and Wladman 2010), tCho is suitable for monitoring tumor carcinogenesis (Guillevin et al 2008;Housni and Boujraf 2013). In previous study it was reported that the 45% increase of tCho indicates tumor progression, while an increase of up to 35% indicates its stable status (Pinker et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectral editing using BASING has previously been applied at 1.5T to obtain spectroscopic images of lactate distribution in the brain (17,18). Li et al (17) merely scored the presence or absence of lactate in spectroscopic imaging voxels without attempting quantification, while Lupo et al (18) reported peak heights normalized to the size of the noise.…”
mentioning
confidence: 99%
“…Li et al (17) merely scored the presence or absence of lactate in spectroscopic imaging voxels without attempting quantification, while Lupo et al (18) reported peak heights normalized to the size of the noise. While this appeared to work reasonably well at 1.5T using a standard quadrature head coil, the worsened B 1 field homogeneity at 3T demands more rigorous signal normalization.…”
mentioning
confidence: 99%